Career Guidance for Unaccompanied Young Migrants. A Report on an Italian Experience - Paola Magnano; Andrea Zammitti (Journal for Perspectives of Economic Political and Social Integration, 2020)
Unaccompanied foreign minors are migrant children without their parents, relatives, or other adults. In Italy, especially in Sicily, an increasing number of young, non-European Union foreigners arrive daily in search of a new life and work opportunities. Despite this increasing phenomenon, interventions to support young migrants in career projects are infrequent and occasional within the host communities. With the aim of developing a career guidance intervention suitable for unaccompanied foreign minors, we propose a case study presenting a career guidance intervention for a group of unaccompanied foreign adolescents. The framework is the life design paradigm. The conductors of the activities were career counsellors, with the support of a cultural mediator and/or an educator. The setting of the interventions was individual and small groups. The instruments and procedures were predominantly qualitative. This paper includes a discussion of the strengths and weakness of this intervention, including the results of the post-intervention evaluation and the follow-up after one year.